PENDIDIKAN AGAMA HINDU SEBAGAI DASAR PENANAMAN NILAI MORAL DAN ETIKA ANAK SEJAK DINI PADA KELUARGA HINDU - IG Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Children are the successors of the family and nation generation, need to get a goodeducation so that their potentials can develop rapidly, so that they will grow into human beingswho have a strong personality and have various kinds of abilities and useful skills. Therefore itis important for families, educational institutions play a role and are responsible for providingvarious kinds of stimulation and appropriate guidance so that it will create a strong nextgeneration. Moral Education and Religious Values in Early Childhood: Not Just Routines. Lately,various negative behavioral phenomena are often seen in everyday life in children. Throughnewspapers or television found cases of early childhood who speak impolite, like to imitateviolent scenes, also imitate the behavior of adults that should not be done by children, evensuicidal behavior has begun to be imitated by children. This condition is very concerningconsidering the world of children should be a world full of pleasure to develop themselves, mostof which is filled with learning through various games in the surrounding environment.